Competency-Based Rubrics for Effective Talent Selection in College Recruitment - Wen-Li, Chyr; Chang, Shu-Ching; Yi-Fei Chuang; Lee, Lynne (Jiao yu ke xue yan jiu qi kan, 2024)
[LANGUAGE=”English”] The historical trajectory of Taiwan’s university entrance examination system has culminated in a multifaceted platform for admission. This evolution is directly attributable to the implementation of the 2019 new curriculum guidelines of 12-year basic education. Aligned with the curriculum’s emphasis on cultivating nationally competitive talents, the traditional entrance examination has been replaced by holistic evaluation of students’ learning portfolios. Consequently, senior high school students’ learning portfolios play a crucial role in the admission process. The reformed curriculum is centered on core competencies, fostering student aptitude and adaptability through a multifaceted approach encompassing enrichment electives, diversified electives, school-developed curricula, cross-domain interdisciplinary learning, flexible learning, self-directed learning, and independent learning. This fundamental shift prioritizes individualized learning opportunities. Moreover, to stimulate student engagement, the curriculum and pedagogy emphasize rich, adaptable, diverse and cross-disciplinary learning opportunities. Considering the core competencies framework of the 2019 curriculum, college recruitment should not rely solely on advanced subject tests as selection criteria. Instead, comprehensive evaluations of the student-centered learning process are imperative. Such evaluations enable a holistic education philosophy that integrates learning and life. Talent selection by using professional competency-based rubrics necessitates the collection of diverse materials and focuses on the learning process. Accordingly, a competency-based portfolio assessment and selection methodology should be established. To this end, the talent selection mechanism for college recruitment should contextualize the student learning process, emphasize characteristic review, and facilitate the development of a robust positioning mechanism and professional assessment competencies, which are essential components of curriculum reform success.The implementation of Taiwan’s 2019 curriculum has engendered a diverse educational landscape characterized by varying school profiles and student learning trajectories and encompasses school-developed curricula, specialized electives, on-campus and off-campus engagements, flexible and self-directed learning, competitions, standardized tests, and certifications. Multifaceted experiences such as these are systematically documented in student learning portfolios and complemented by a teacher certification mechanism. To effectively evaluate these diverse portfolios, reviewers require not only specialized expertise but also refined assessment tools capable of meeting societal demands for enhanced review quality and public trust. This case study elucidated the development of competency-based rubrics through focus group interviews and empirical research and identified critical rubric components for talent selection. By understanding these criteria, students can strategically cultivate attributes valued by higher education institutions during their senior high school years.Portfolio assessment has been identified as a pivotal evaluation methodology in the Taiwanese education landscape. This study bridged the gap between university competency-based selection and senior high school talent cultivation through the lens of portfolio assessment. The study involved an examination of the perspectives and opinions of both stakeholders. By conducting a case study, focus group interviews, and a historical review of portfolio assessment rubrics, the study developed appropriate rubrics for university selection and high school talent development. Given the nascent nature of portfolio assessment tool development and calibration in the Taiwanese educational context, a case study methodology was employed to investigate the rubric creation processes of various university departments. This approach is well suited for addressing complex and underresearched problems and for exploring what to do, how to do it, and why to do it, thereby offering in-depth, multifaceted insights. Focus group interviews, a core component of the case school’s rubric development, facilitated dialogue between university and high school teachers, fostering a comprehensive understanding of portfolio assessment and culminating in the development of competency-based rubrics through collective input. Finally, this study verifies the validity of said competency-based rubrics through empirical research.The study findings reveal that competency-based rubrics developed by university departments, aligned with their educational objectives, effectively mirror the core competency emphasis of the 2019 curriculum reform. Although rarely used in college recruitment, portfolio assessment is widely used by teachers to examine student performance and assessment results. This research demonstrates the efficacy of assessing students across diverse learning domains. To address the challenge of appropriate talent selection, this study expands the traditional archival assessment approach. Focus group interviews involving university and high school faculty facilitated the refinement of competency-based rubric dimensions and promoted portfolio assessment. These interviews also fostered consensus on rubric connotations. Such dialogue between universities and senior high schools enabled universities to grasp the core competencies and multiple intelligences cultivated in high schools, whereas the senior high schools gained insights into the characteristics and skills required for university success. This study pioneers the application of focus group interviews in the development of competency-based rubrics for college admissions. Finally, the results of the correlation analysis of pre-enrollment and postenrollment student performance informed calibration of the rubric and the enhancement of its effectiveness. A dynamic correction process, incorporating a Plan-Do-Check-Action mechanism, was introduced for rubric verification and calibration. This innovative approach addresses the limitations of other evaluation rubric correction methods. The study results provide a foundation for senior high school students to cultivate university-aligned talents and offer a model for university departments to develop suitable competency-based rubrics for student selection.[LANGUAGE=”Chinese”] 大學選才制度在多次的改革下，朝向多元入學方式邁進。而隨著108課綱的推動，在這波關係到未來人才培育和國家競爭力的教育改革中，蒐集學生多元表現之學習歷程檔案逐漸成為入學審查的主要考量方式之一，其扮演極為重要的角色。有鑑於學習歷程檔案評量法（portfolio assessment）在臺灣教育情境中已日漸受到青睞並被多元運用，本研究旨在探討如何應用學習歷程檔案評量搭起建立大學選才與高中育才之間的橋梁，期藉由個案學校說明如何藉由焦點團體訪談以及實證研究等方法，瞭解大學招生專業化素養導向的招生選才觀點與看法，提出學習歷程檔案評量工具的發展歷程與校準。本研究結果發現，大學端依據學系教育目標培養之職能設計評量尺規，能呼應108課綱強調培養核心素養之精神；此外，大學端與高中端藉由焦點團體訪談的對話，有助於尺規向度描述之適當性與宣導尺規評量；最後，透過對學生在高中時期各方面表現和進入大學後表現的相關性分析結果，進行評量工具校準，以提升評量尺規之有效性。本研究之結果與意涵可供高中端作為進入大學前育才之依據，以及大學系所發展適宜選才評量工具之參考。